Effectiveness of interventions to maintain physical activity behavior (device‐measured): Systematic review and meta‐analysis of randomized controlled trials. (15th June 2021) - Madigan, Claire D.; Fong, Mackenzie; Howick, Jeremy; Kettle, Victoria; Rouse, Peter; Hamilton, Louisa; Roberts, Nia; Gomersall, Sjaan R.; Daley, Amanda J.
Summary: Physical activity has many physical, mental, and social health benefits. Interventions can be successful at helping people initiate participation, but there is a lack of evidence about the ability of these interventions to help adults maintain their physical activity. This systematic review and meta‐analysis aims to address this evidence gap. We investigated the extent to which successful physical activity interventions with demonstrated success within randomized controlled trials result in maintenance of device‐measured physical activity (at least 3 months post‐intervention end). Five databases were searched, and 8919 titles and abstracts were screened for eligibility, and 29 trials met the inclusion criteria. Of these, 22 were included in the meta‐analysis. We found that 60% to 80% of physical activity behavior was maintained, as equivalent to an additional 45 min/week of moderate‐to‐vigorous physical activity and 945 steps per day compared with comparators. We also examined trials that randomized participants to maintenance interventions after an initial physical activity intervention (n = 7) and we found small effects (standardized mean difference 0.14, 95% confidence interval [CI] 0.1 to 0.27). The evidence suggests that most (60%–80%) of the increases in physical activity in successful programs are maintained for at least 3 months and there are small effects from providing a maintenance intervention to the public. Registration: CRD42019144585.